Eating disorder risk in adolescents with obesity. (6th January 2021) - Jebeile, Hiba; Lister, Natalie B.; Baur, Louise A.; Garnett, Sarah P.; Paxton, Susan J.
Summary: The intersection between adolescent obesity and eating disorder risk is one that requires urgent attention. This review aimed to synthesize the literature on the risk of clinical eating disorders in adolescents with obesity, discuss challenges with assessing risk, and examine implications for clinical practice and future research. Obesity and eating disorders can coexist resulting in exacerbated physical and psychological health issues. Recognized eating disorder risk factors, including body dissatisfaction, poor self‐esteem, depression, and engaging in dieting behaviors, are elevated and frequently reported in adolescents with obesity, highlighting a vulnerability to the development of eating disorders. Unsupervised dieting to manage weight may exacerbate eating disorder risk, while structured and supervised weight management is likely to reduce eating disorder risk for most adolescents. However, some adolescents may present to an obesity service with an undiagnosed eating disorder or may develop an eating disorder during or following treatment. We conclude that a risk management approach, with screening or monitoring for eating disorder‐related risk factors and behaviors, should be utilized to identify those at risk. Future research to identify eating disorder risk factors specific to adolescents with obesity is required to inform screening and monitoring protocols, patient care, and address current knowledge gaps.